(3JbSje GdYdhe hEKHGJ GdMb hcTa Gdecfhfs - (3CHh EHQGgje ESeGYjd Hf eMeO Hf MGeO GdJejej,J (B420 (3g` s
(3ChdgG (B:s
(3JCdja ESeGYjd Hf eMeO s
(3BNQgG (B:s
(3Je cJGH JbSje GdYdheq s
(3Vef eLehY , JQJjHgG (B: 22s
(3GdeDda ef OYGI GdHGWfjIs
(3hdg YfO GdOQRjI ebGe cHjQs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdJhMjO hGdedd hGdfMds